A Survey of K-12 Teachers’ Perspectives on Teaching with Generative Artificial Intelligence - Gary Andersen; Sohyun Yang (The Advocate, 2025)
This study investigated K–12 educators’ perceptions of generative artificial intelligence (GenAI) in teaching and learning, examining how teachers use and evaluate GenAI tools in relation to student thinking and classroom practices. Grounded in Bloom’s Taxonomy (1956) and Ritchhart’s (2015) Cultures of Thinking framework, the survey of 73 teachers revealed that while most participants use GenAI for instructional design and administrative efficiency, far fewer employ it to foster higher-order cognitive processes such as application, analysis, and evaluation. Teachers reported benefits in lesson planning and differentiation but expressed concerns about accuracy, ethics, and overreliance. Findings highlighted a critical need for professional development that integrates technical proficiency with pedagogical strategies for using GenAI to promote application, critical thinking, and deeper student learning. The study underscores that GenAI’s educational potential remains underrealized without intentional alignment to human-centered teaching goals.
Keywords: generative artificial intelligence (GenAI); K-12 educators; professional development; pedagogy